Melanoma Antigen Gene Protein MAGE-11 Regulates Androgen Receptor Function by Modulating the Interdomain Interaction - Bai, Suxia (American Society for Microbiology, 2005)
Gene activation by steroid hormone receptors involves the recruitment of the steroid receptor coactivator (SRC)/p160 coactivator LXXLL motifs to activation function 2 (AF2) in the ligand binding domain. For the androgen receptor (AR), AF2 also serves as the interaction site for the AR NH(2)-terminal FXXLF motif in the androgen-dependent NH(2)-terminal and carboxyl-terminal (N/C) interaction. The relative importance of the AR AF2 site has been unclear, since the AR FXXLF motif interferes with coactivator recruitment by competitive inhibition of LXXLL motif binding. In this report, we identified the X chromosome-linked melanoma antigen gene product MAGE-11 as an AR coregulator that specifically binds the AR NH(2)-terminal FXXLF motif. Binding of MAGE-11 to the AR FXXLF α-helical region stabilizes the ligand-free AR and, in the presence of an agonist, increases exposure of AF2 to the recruitment and activation by the SRC/p160 coactivators. Intracellular association between AR and MAGE-11 is supported by their coimmunoprecipitation and colocalization in the absence and presence of hormone and by competitive inhibition of the N/C interaction. AR transactivation increases in response to MAGE-11 and the SRC/p160 coactivators through mechanisms that include but are not limited to the AF2 site. MAGE-11 is expressed in androgen-dependent tissues and in prostate cancer cell lines. The results suggest MAGE-11 is a unique AR coregulator that increases AR activity by modulating the AR interdomain interaction.